Super modern diabetic foot surgery - Amit Kumar C Jain (Medicine Science, 2021)
Significant developments have taken place in field of diabetic foot over past few years. This was considered to be a neglected condition both by the patients and the treating clinicians. Owing to the fact that diabetic foot can lead to amputation which may cause debilitation of the patient, awareness of this condition has been on raise over past decade. Diabetic foot being a complex disease often has many difficulties in understanding it and also there have been treatment dilemmas. Recently, a new principle and practice was laid down for this condition from India, known as Amit Jains system of practice, which is now the modern diabetic foot surgery. There has been addition of various new eponymous works by the author to this new system, thereby taking a leap into super modern diabetic foot surgery system. This brief article highlights on few of these new eponymous works of the author on super modern diabetic foot surgery. [Med-Science 2021; 10(3.000): 1081-4]